Design a Patient Medical Record Application to Shorten Registration Time Using the Waterfall Model - Putry Sandi Felicia; Nina Zaitun (Jurnal Riset Ilmu Teknik, 2023)
Health agencies need speed of information services and provide optimal service to customers. The patient medical record procedures at the Rohil Medika Clinic, from patient registration to making daily reports, still use a manual system, so activities are ineffective and inefficient. The research aims to produce a design for a Web-Based Patient Medical Record Application at the Rohil Medika Clinic, which makes monthly patient visit report information and patient medical record report information that aligns with the needs of the Rohil Medika Clinic. The data collection method was obtained by observing and interviewing Rohil Medika Clinic Leaders and other medical workers. Data processing begins with evaluating the Clinic's needs and then designing the system design, interface, system coding (implementation), and conducting system testing. The research results based on trials show that the application can handle patient administration, patient examinations, and patient medical records and save time searching patient data by up to 67.6% to 90.9%. Medical record applications also increase clinical services from 25 patients to 45 patients/day to 45 patients to 95 patients/day. The system can also provide information on daily and monthly patient visit reports, medical records, and patient data reports.